1970
DOI: 10.1042/bj1190265
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a cross-bridging thiol reagent on the catecholamine fluxes of adrenal medulla vesicles

Abstract: The thiol groups of the vesicular protein of bovine adrenal medulla were allowed to react with the bifunctional thiol reagent bis-(N-maleimidomethyl) ether and with the monofunctional thiol reagent N-ethylmaleimide, and the ATP-dependent and -independent catecholamine fluxes of the modified preparations were studied. 1. During the initial phase of the reaction bis-(N-maleimidomethyl) ether blocks twice as many thiol groups as does N-ethylmaleimide at equimolar concentrations. 2. Labelling of the bis-(N-maleimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

1971
1971
1988
1988

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…NEM did not have significant effect on catecholamine efflux. These results are comparable to those of Hasselbach and Taugner (3). The reduction in the SCN-concentration ratio by NEM corresponds to a 10-mV decrease in electrical potential.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…NEM did not have significant effect on catecholamine efflux. These results are comparable to those of Hasselbach and Taugner (3). The reduction in the SCN-concentration ratio by NEM corresponds to a 10-mV decrease in electrical potential.…”
Section: Methodssupporting
confidence: 80%
“…Because the in vitro rate of uptake of catecholamines into chromaffin vesicles is increased severalfold by ATP and magnesium (1), it had been thought that the Mg2+-dependent ATPase associated with the vesicle membrane is a catecholamine transport enzyme. Although partial correlations have been obtained between ATPase activity and catecholamine transport (2,3), lack of a simple quantitative correlation suggests that the ATPase may be indirectly rather than directly involved.…”
mentioning
confidence: 99%
“…Isolated granules catalyze ATP-dependent uptake of massive amounts of epinephrine (5,6), and the process is inhibited by proton conductors (7). ATPase activity (8)(9)(10)(11), ATP-dependent proton translocation (12), and ATP-dependent changes in the fluorescence of 1-anilino naphthalene-8-sulfonate (ANS) (11) have been detected in intact granules or membrane vesicles prepared from chromaffin granules by osmotic shock. Moreover, it has been demonstrated that an uncoupler-sensitive pH gradient (ApH, interior acid) is maintained across the chromaffin granule membrane (13)(14)(15).…”
mentioning
confidence: 99%
“…After 10 min, the vesicles were collected by centrifugation at 40,000 X g for 10 min. The procedure was repeated once, and the chromaffin granule membrane vesicles were suspended in 0.3 M sucrose containing 10 size). The filters were then washed with another 2 ml of the latter solution, removed from the suction apparatus, dried, and assayed for radioactivity by liquid scintillation spectrometry.…”
mentioning
confidence: 99%
“…Another inhibitor of Mg + +-ATPase activity, N-ethyl maleimide (NEM) also blocks the uptake of NE by isolated vesicles (Hasselbach and Taugner, 1970) and pre- Fig. 1.…”
Section: Methodsmentioning
confidence: 99%